Variability In Response Of Indian Fodder Legume (Medicago Sativa) To Salt Stress On Physiological Attributes - SHAILY BHARDWAJ; K.A.VARSHNEY; N. K. SHARMA; GAURAV SHUKLA (International Journal of Pharma and Bio Sciences, 2011)
Several biochemical processes of plants are affected adversely by soil salinity. In order to understand the mechanism of salt tolerance in Medicago sativa L. (Lucerne) an important fodder legume, present study was sought on enzyme activity at different levels of electrical conductivity of soil. Nitrate reductase activity and total nitrogen was inhibited by salinity. Where nitrite reductase and nitrogenase activity were observed increasement in their activity. The study with NaCl salinity was chosen as the North West belt of Uttar Pradesh (India) was found saline. It was done by chemical analysis of soil and plants collected from various sites of Rohilkhand division (Bareilly, UP).